2019
DOI: 10.1021/acscatal.9b04424
|View full text |Cite
|
Sign up to set email alerts
|

Symmetrical Exsolution of Rh Nanoparticles in Solid Oxide Cells for Efficient Syngas Production from Greenhouse Gases

Abstract: Carbon dioxide and steam solid oxide co-electrolysis is a key technology for exploiting renewable electricity to generate syngas feedstock for the Fischer-Tropsch synthesis. The integration of this process with methane partial oxidation in a single cell can eliminate or even reverse the electrical power demands of co-electrolysis, while simultaneously producing syngas at industrially attractive H2/CO ratios. Nevertheless, this system is rather complex, and requires catalytically active and coke tolerant electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 58 publications
3
46
0
Order By: Relevance
“…This of course poses additional requirements as to the exact conditions as far as the oxygen partial pressure (pO 2 ) of the gas, the temperature of the reduction as well as the ramping rate to the required temperature. [41] Depending on the materials studied it has been shown that high temperature leads to low particle population and larger particle size [33,42,43] while one can have an impact on the nature of the exsolved species by changing the type of the reducing gas (Figure 11). [22] For example, reduction under CO atmosphere could produce cubic particles while slightly humidified H 2 can lead to the exsolution of nanorods or even heterostructures.…”
Section: Extrinsic Factorsmentioning
confidence: 99%
“…This of course poses additional requirements as to the exact conditions as far as the oxygen partial pressure (pO 2 ) of the gas, the temperature of the reduction as well as the ramping rate to the required temperature. [41] Depending on the materials studied it has been shown that high temperature leads to low particle population and larger particle size [33,42,43] while one can have an impact on the nature of the exsolved species by changing the type of the reducing gas (Figure 11). [22] For example, reduction under CO atmosphere could produce cubic particles while slightly humidified H 2 can lead to the exsolution of nanorods or even heterostructures.…”
Section: Extrinsic Factorsmentioning
confidence: 99%
“…As shown in Table 4 , these reported exsolution materials include single metal particles composed of Ni, [ 68,115–122 ] Cu, [ 92 ] Co, [ 81 ] Fe, [ 135–137 ] and Rh. [ 108 ] Such materials also encompass alloys, such as Fe–Ni, [ 101,102,144,145 ] Ni–Cu, [ 105,152 ] Co–Ni, [ 150 ] and Co–Fe. [ 101,154–156 ] For the electrolysis of pure CO 2 gas, exsolution materials were generally used as the cathode electrodes of SOECs.…”
Section: Performance Of Exsolution Materials For the Conversion Of Smmentioning
confidence: 99%
“…Besides water, some researchers put CH 4 gas into the anode to assist CO 2 electrolysis in SOECs. [ 105,108 ] This reaction combined CO 2 electrolysis (CO 2 + 2e − = CO + O 2− ) with CH 4 electrochemical oxidation (CH 4 + O 2− = CO + 2H 2 + 2e − ) in a simultaneous process. Lu et al.…”
Section: Performance Of Exsolution Materials For the Conversion Of Smmentioning
confidence: 99%
“…An impressive application for exsolution electrodes is for the co-generation of valuable chemical products (CH 4 , CO, H 2 ) and electricity. Ru exsolution from La 0.43 Ca 0.37 Rh 0.06 Ti 0.94 O 3 was shown to be effective at co-electrolysis (where CO 2 and H 2 O are reduced to CO and H 2 at the cathode), CH 4 -assisted co electrolysis (where CH 4 is simultaneously oxidized to CO 2 and H 2 O at the anode via O 2− transport) and co-generation, where the reversible potential becomes negative and electricity and chemical products are produced together [52]. In addition to the examples cited above, a partial summary of the advancements made in the design of exsolution electrodes is given in Table 1.…”
Section: Recent Advancements In Exsolution Electrodesmentioning
confidence: 99%